IMPROVING STUDENTS’ VOCABULARY USING APPLICATION “RUANG GURU” AT SMPN 35 MAKASSAR - Ronal Simon; Ulfah Syam; Rampeng (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
RONAL SIMON 2022. IMPROVING STUDENTS’ VOCABULARY USING APPLICATION “RUANG GURU” AT SMPN 35 MAKASSAR. Skripsi of the English Education Study Program, Faculty of Teacher Training and Education, Bosowa University. (Supervised by Ulfah Syam, and Rampeng. The aim of this research is conducted in order to improve students’ vocabulary through Ruang Guru application at the first grade of SMPN 35 Makassar. This study was experimental research with a pre-experimental One Group Pre-test and post-test research design, namely giving a test before treatment, then giving a test after treatment using the Ruang Guru application. The sample of this study was is grade VII.2 students. A total of 23 students. The research was conducted in 4 meetings. The data collection technique used in the study was a test technique which was analyzed with descriptive statistics. The data obtained were also analyzed using SPSS version 22.0 program. The results showed that there was an effect of the learning model using the Ruang Guru application on the learning students at VII.2 SMP Negeri 35 Makassar. This can be seen based on the results of the SPSS version 22 analysis.